The Influence of Principals’ Instructional Leadership and Teachers’ Work Motivation on the Pedagogical Competence of Elementary School Teachers - Susilo Adi Saputro; Nur Khoiri; Lilik Ariyanto (Papanda Publisher, 2026)
The drop in the 2024 education report cards for Gayamsari District, Semarang City, suggests that pedagogical skills among teachers in several elementary units remain suboptimal. The primary objective of this research is to assess how principal instructional leadership and teacher work motivation impact the pedagogical competence of elementary educators within this region. This research employed a quantitative methodology utilizing a correlational design. A sample of 135 public elementary school teachers was selected for this study using the proportional random sampling technique. Validated and reliable questionnaires were utilized to gather data concerning three key variables: instructional leadership, work motivation, and pedagogical competence. Following the fulfillment of classical assumption tests, the data were analyzed using multiple linear regression. Findings reveal that instructional leadership exerts a positive and significant influence on pedagogical competence, evidenced by a calculated t-value of 5.621. Similarly, teacher work motivation demonstrates a significant positive impact on pedagogical competence, with a t-value of 4.516. When analyzed together, both instructional leadership and work motivation significantly affect pedagogical competence, indicated by an F-value of 17.928 and an R-squared value of 0.214. Consequently, these two factors account for 21.4% of the variance in pedagogical competence, leaving the remaining 78.6% attributed to external factors not covered in this study. These results underscore that reinforcing learning-oriented leadership and boosting work motivation are vital, complementary strategies for elevating the pedagogical competence of elementary school teachers.